Amigdalectomía en pacientes con asimetría amigdalina: análisis histopatológico y factores de riesgo de malignidad - Walker J., Katherine; Aguirre R., Noemí; Molina C., Víctor; Bustamante Y., Carolina (Revista Hospital Clínico Universidad de Chile, 2011)
Introduction: Tonsillectomy is the most frequent ENT (ear nose and throat) surgery. An absolute indication is suspicion of a malignant tumor. Therefore the importance of determine whose patients are inherent to that risk. Objective: To conduct a histopathological analysis of asymmetrical tonsillar biopsies, correlate clinical suspicion of tumor with biopsy results, and compare patients with exclusive tonsillar asymmetry versus tonsillar asymmetry plus others symptoms or signs suggestive of malignant pathology. Methods: Retrospective analysis of tonsillar biopsies processed from patients diagnosed with tonsillar asymmetry at HCUCH (Hospital Clínico Universidad de Chile), February 2003 through June 2006 period. Two groups were selected: Exclusive tonsillar asymmetry (Group A) and asymmetry associated with clinical findings suggestive of malignancy (Group B). Results: 2083 Tonsillectomies, from which 135 (6,48%) where sent to biopsy. Of these, 41 (30,3%) had been diagnosed as tonsillar asymmetry (2% from total). 23 female and 18 male, age range: 2- 73 years old, (Average age: 27 years), 9 patients had tonsillar asymmetry associated to a clinical suspicion finding of malignant pathology, while 32 patients had exclusive asymmetry. Group A histopathological analysis informed as Chronic Inflammation in 24 cases (75%), chronic inflammation plus actinomyces presence in 8 cases (25%), no malignant pathology; correlation Obs. Tumor/Real tumor: 4/0 = 0%. Group B histopathological analysis informed as chronic inflammation: 4 (44,4%), chronic Inflammation plus actinomyces presence 2 (22,2%), Squamous papilloma 1 (11,1%), Squamous Carcinoma 1 (11,1%), Lymphoma 1 (11,1%); correlation Obs. Tumor/Real Tumor: 6/3 = 50%. Discussion: Tonsillar asymmetry corresponded to 31% of tonsillectomies prescriptions in our center. If tonsillar asymmetry is associated to risk factors or clinical finding suggestive of malignancy, prescription of tonsillectomy is clear, due to a clinical correlation of 50%. Prescription of tonsillectomy in exclusive tonsillar asymmetry is debatable, as the anathomopathological study in all cases.